Nucleic acid nanotechnology - Ferapontova, Elena; Gothelf, Kurt V.; Kjems, Jorgen (Nucleic Acids and Molecular Biology, 2014)
This volume on nucleic acid nanotechnology offers authoritative, up-to-date and comprehensive coverage of nanotechnological studies and applications of nucleic acids. It provides reviews of various aspects of nucleic acid nanotechnology, each written by an internationally leading expert in the field, and presents state-of-the-art and recent advances in nucleic acid synthetic modifications, nanoscale design, manipulation and current and future applications in bioengineering, medicine, electronics, genetic analysis, chemistry, molecular biology, surface and material sciences. It examines how nucleic acid research is merging with nanotechnology, allowing the nanoscale properties of nucleic acid to be exploited in performing challenging nanotechnological tasks, from nanorobotics and nanosensing to nucleic acid computing. This book will above all benefit anyone who is interested in nanotechnological concepts of nucleic acid design and applications, and offers a valuable resource for teaching these concepts. It is essential reading for a broad audience of scientists both in academia and industry who wish to expand their expertise on the potential of nucleic acid functions and applications.